Ag⁺‐Mediated Structural Reconstruction of a Metastable Cu 35 Cluster Toward Cu–Ag Heterometallic Architectures for Superior Electrocatalytic CO 2 ‐to‐Ethanol Conversion - Chen, Xin‐Yu; Li, Lan‐Yan; Zhao, Lan‐Cheng; Liu, Qing‐Yi; Ding, Dang‐Dang; Zhang, Li‐Li; Sun, Xiao‐Yan; Wang, Li‐Kai; Mo, Hong‐Bing; Yan, Jun; Liu, Chao (Angewandte Chemie International Edition, 2025)
Controlled structural transformations of metal nanoclusters (NCs) via dynamic bond reorganization provide fundamental insights into cluster reactivity and open avenues for functionality tuning. Here, we report a thiacalix[4]arene‐protected Cu(I)‐alkynide cluster, {NaCu 35 (TC4A) 4 (Ph‐C≡C) 20 } ( Cu 35 ), which exhibits remarkable structural plasticity. This metastable cluster can grow into a Cu 36 species via ion substitution or undergo thermal‐induced fragmentation to form a smaller Cu 14 cluster. Under thermal etching by Ag + ion, structural reconstruction is triggered, leading to the formation of the bimetallic Cu 14 Ag 6 and Cu 40 Ag 16 clusters. The structural reorganization significantly alters the catalytic outcomes in electrocatalytic CO 2 reduction. Although the monometallic Cu 35 and Cu 14 favor gaseous CH 4 /C 2 H 4 production, the bimetallic Cu 14 Ag 6 demonstrates remarkable selectivity for ethanol synthesis. Notably, Cu 14 Ag 6 achieves an impressive Faradaic efficiency (FE) of 49.27% for ethanol production, alongside a high partial current density of −67.94 mA cm −2 . This marks the highest ethanol selectivity reported to date for atomically precise cluster catalysts. Mechanistic investigations reveal that, compared to homometallic Cu⋯Cu dual sites (which typically favor C 2 H 4 ), the unique Ag⋯Cu⋯Cu trimetallic microstructure in Cu 14 Ag 6 is more thermodynamically favorable for asymmetric C─C coupling between *CHO and *OCH 2 , facilitating the formation of the key *CHO−*OCH 2 intermediate, which drives the ethanol‐selective pathway.